Pengaruh Penerapan Tata Tertib Terhadap Kedisiplinan Peserta Didik di SMK Bina Pangudi Luhur Jakarta - Azizah, Evi Nur; Firdaus, Firdaus; Ulfah, Maria (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research is motivated by the fact that students' indiscipline in following school rules often becomes a problem, especially at the secondary school level, when students grow up and begin to learn to recognize their identity through imitation or self-imitation. To overcome this problem, sanctions are imposed. The purpose of imposing sanctions is to provide a deterrent effect to students who violate the rules to anticipate repetition of rule violations by students. The research method in this study is the